Low-loss ultrafine soft magnetic alloy powder and its production method and application
By phosphating treatment and silica coating on the ultrafine soft magnetic alloy powder, combined with sodium sulfonate salt derivatives and acylphosphate derivatives as phosphating additives, the problem of high power loss of ultrafine soft magnetic materials in the medium and high frequency range is solved, and the manufacturing of low-loss ultrafine soft magnetic alloy powder with high resistivity and low power loss is achieved.
Patent Information
- Application Number
- CN202510070276.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The existing ultra-fine soft magnetic materials have high power loss in the medium and high frequency range, and it is difficult to achieve uniform coating in the inorganic insulation coating process, resulting in deterioration of soft magnetic properties.
The ultrafine alloy powder is obtained by melting iron, nickel, manganese, aluminum, silicon and chromium at high temperature, and evaporation condensation method is used to obtain an ultrafine alloy powder. Then, the medium-temperature zinc-manganese-based phosphating liquid is phosphating, and the silica insulating layer is coated with 3-aminopropyltriethoxysilane and ethyl orthosilicate, and the sodium sulfonate salt derivative and acylphosphate derivative are used as phosphating additives to increase the resistivity of the alloy powder.
The manufacturing of low-loss ultra-fine soft magnetic alloy powder is achieved, with the resistivity increased to 9.0-18.2Ω·cm and the power loss reduced to 282.3-320.3mW/cm3, which is suitable for the preparation of high-performance inductors.
Smart Images

Figure CN119480423B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soft magnetic materials, and in particular to low-loss ultrafine soft magnetic alloy powder and a manufacturing method and application thereof. Background Art
[0002] Ultrafine soft magnetic materials are usually composed of metal magnetic powder and surface insulating coating medium. Compared with traditional soft magnetic materials, they have better soft magnetic properties and lower power loss in the medium and high frequency range, and have better processing and forming properties. Therefore, ultrafine soft magnetic materials are widely used in inductors, transformers and electric drive devices. With the development of high-frequency and high-power electronic technology, the operating frequency of electronic devices has gradually increased, and ordinary soft magnetic materials cannot meet the requirements. An effective solution is to increase the resistivity of magnetic powder insulation coating treatment, thereby reducing the power loss of ultrafine soft magnetic materials. Insulation coating can be roughly divided into organic coating and inorganic coating. The coating process of organic coating medium is simple, but it usually has poor thermal stability and may decompose during annealing. Therefore, the ultrafine soft magnetic material obtained after organic insulation coating treatment usually has a low annealing temperature, and the internal stress generated during the pressing process is difficult to completely release, and it is difficult to obtain ultrafine soft magnetic materials with high effective magnetic permeability. The inorganic coating medium is simple to operate, but it is difficult to coat the channel uniformly. It is easy to break and fall off when annealed at a higher temperature, and even decompose, causing the deterioration of soft magnetic properties. Therefore, a new method for manufacturing low-loss ultrafine soft magnetic alloy powder is needed to obtain low-loss ultrafine soft magnetic alloy powder with excellent soft magnetic properties. Summary of the invention
[0003] The purpose of the present invention is to provide low-loss ultrafine soft magnetic alloy powder and its manufacturing method and application, so as to achieve the effect of improving the resistivity of soft magnetic materials and reducing power loss.
[0004] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0005] A method for producing low-loss ultrafine soft magnetic alloy powder, comprising:
[0006] S1. Iron, nickel, manganese, aluminum, silicon and chromium are smelted into an alloy at high temperature, and the alloy is heated to boiling point by evaporation condensation method, and then steam cooled to obtain ultrafine alloy powder with a D50 particle size of 100-3000nm;
[0007] S2, reacting the ultrafine alloy powder with a medium-temperature zinc-manganese phosphating solution and a phosphating aid, and then reacting with 3-aminopropyltriethoxysilane and ethyl orthosilicate to obtain a low-loss ultrafine soft magnetic alloy powder;
[0008] The phosphating auxiliary agent at least includes a sodium sulfonate derivative, and the sodium sulfonate derivative has a sulfonic acid group, a benzene ring and a vinyl group.
[0009] The invention melts iron, nickel, manganese, aluminum, silicon and chromium into an alloy, and then obtains alloy powder by an evaporation condensation method; then, a medium-temperature zinc-manganese phosphating solution and a phosphating auxiliary agent are used to perform phosphating treatment on the alloy powder to form a phosphating layer on the surface of the alloy powder; and then, 3-aminopropyltriethoxysilane and ethyl orthosilicate are used to coat a silicon dioxide insulating layer on the surface of the alloy powder; the phosphating auxiliary agent of the invention comprises a sodium sulfonate derivative, and the sodium sulfonate derivative has a large number of hydrophilic groups, which can enhance the wetting performance of the phosphating solution on the surface of the alloy powder, thereby not only ensuring the phosphating film-forming speed and obtaining a better coating effect, but also improving the soft magnetic properties, thereby achieving the effect of improving the resistivity of the low-loss ultrafine soft magnetic alloy powder and reducing the power loss.
[0010] Preferably, the mass ratio of iron to nickel is 1:1-2, the mass ratio of iron to manganese is 1:0.001-0.02, the mass ratio of iron to aluminum is 1:0.001-0.02, the mass ratio of iron to silicon is 1:0.001-0.02, and the mass ratio of iron to chromium is 0.001-0.02.
[0011] Preferably, the mass concentration of the medium-temperature zinc-manganese phosphating solution is 5-10%, and the usage ratio of the ultrafine alloy powder to the medium-temperature zinc-manganese phosphating solution is 1g:1-2mL.
[0012] Preferably, the usage ratio of the ultrafine alloy powder to 3-aminopropyltriethoxysilane is 1 g: 0.1-0.5 mL.
[0013] Preferably, the volume ratio of ethyl orthosilicate to 3-aminopropyltriethoxysilane is 1:2-10.
[0014] Preferably, in the preparation of the sodium sulfonate derivative, azelaic acid chloride and 1-octen-3-ol are first reacted, and then sodium bisulfite is added to react to obtain the sodium sulfonate derivative.
[0015] Preferably, the molar ratio of azelayl chloride to 1-octen-3-ol is 1:1-2.
[0016] Preferably, the molar ratio of azelayl chloride to sodium bisulfite is 1:1-2.
[0017] Preferably, the preparation of the sodium sulfonate derivative is specifically,
[0018] Weigh azelayl chloride, add dichloromethane and stir to dissolve, add 1-octen-3-ol and triethylamine, stir to react for 6-12 hours, add sodium carbonate solution to adjust the pH to neutral, add sodium bisulfite and deionized water, react at 120-160°C for 2-5 hours, add methanol, filter, rotary evaporate, and dry to obtain a sodium sulfonate derivative.
[0019] More preferably, the usage ratio of azelayl chloride to dichloromethane is 1 mol: 300-400 mL.
[0020] More preferably, the molar ratio of 1-octen-3-ol to azelaic acid chloride is 1:1-2.
[0021] More preferably, the molar ratio of triethylamine to azelayl chloride is 1:1-2.
[0022] More preferably, the molar ratio of azelayl chloride to sodium bisulfite is 1:1-2.
[0023] More preferably, the usage ratio of azelayl chloride to deionized water is 1 mol: 150-200 mL.
[0024] More preferably, the volume ratio of deionized water to methanol is 1:1-2.
[0025] Preferably, the production of low-loss ultrafine soft magnetic alloy powder is specifically as follows:
[0026] S1. Iron, nickel, manganese, aluminum, silicon and chromium are smelted into an alloy at high temperature, and the alloy is heated to boiling point by evaporation condensation method, and then steam cooled to obtain ultrafine alloy powder with a D50 particle size of 100-3000nm;
[0027] S2. At 50-60°C, add anhydrous ethanol to the ultrafine alloy powder prepared in step S1, stir at a speed of 400-600r / min, add 3-aminopropyltriethoxysilane and deionized water, add ethyl orthosilicate, react at 40-60°C for 2-5h, wash with anhydrous ethanol 2-5 times, filter and dry to obtain low-loss ultrafine soft magnetic alloy powder.
[0028] More preferably, the mass ratio of iron to nickel in step S1 is 1:1-2.
[0029] More preferably, in step S1, the mass ratio of iron to manganese is 1:0.001-0.02.
[0030] More preferably, in step S1, the mass ratio of iron to aluminum is 1:0.001-0.02.
[0031] More preferably, in step S1, the mass ratio of iron to silicon is 1:0.001-0.02.
[0032] More preferably, in step S1, the mass ratio of iron to chromium is 0.001-0.02.
[0033] More preferably, in step S2, the usage ratio of the ultrafine alloy powder to anhydrous ethanol is 1 g: 5-10 mL.
[0034] More preferably, in step S2, the volume ratio of 3-aminopropyltriethoxysilane to anhydrous ethanol is 1:30-40.
[0035] More preferably, in step S2, the volume ratio of 3-aminopropyltriethoxysilane to deionized water is 1:4-8.
[0036] More preferably, in step S2, the volume ratio of ethyl orthosilicate to 3-aminopropyltriethoxysilane is 1:3-7.
[0037] Preferably, the production of low-loss ultrafine soft magnetic alloy powder is specifically as follows:
[0038] S1. Iron, nickel, manganese, aluminum, silicon and chromium are smelted into alloy at high temperature, and the metal is heated to boiling point by evaporation condensation method, and then steam cooled to obtain ultrafine alloy powder with a D50 particle size of 100-3000nm;
[0039] S2. At 50-60°C, add the ultrafine alloy powder prepared in step S1 to a medium-temperature zinc-manganese phosphating solution, stir at a rate of 100-300 r / min for 10-30 min, let stand for 5-15 min, filter, rinse with pure water 2-5 times, add anhydrous ethanol, stir at a speed of 400-600 r / min, add 3-aminopropyltriethoxysilane and deionized water, add ethyl orthosilicate, react at 40-60°C for 2-5 h, wash with anhydrous ethanol 2-5 times, filter, and dry to obtain a low-loss ultrafine soft magnetic alloy powder.
[0040] More preferably, the mass ratio of iron to nickel in step S1 is 1:1-2.
[0041] More preferably, in step S1, the mass ratio of iron to manganese is 1:0.001-0.02.
[0042] More preferably, in step S1, the mass ratio of iron to aluminum is 1:0.001-0.02.
[0043] More preferably, in step S1, the mass ratio of iron to silicon is 1:0.001-0.02.
[0044] More preferably, in step S1, the mass ratio of iron to chromium is 0.001-0.02.
[0045] More preferably, in step S2, the mass concentration of the medium-temperature zinc-manganese phosphating solution is 5-10%, and the usage ratio of the ultrafine alloy powder to the medium-temperature zinc-manganese phosphating solution is 1 g: 1-2 mL.
[0046] More preferably, in step S2, the usage ratio of the ultrafine alloy powder to anhydrous ethanol is 1 g: 5-10 mL.
[0047] More preferably, in step S2, the volume ratio of 3-aminopropyltriethoxysilane to anhydrous ethanol is 1:30-40.
[0048] More preferably, in step S2, the volume ratio of 3-aminopropyltriethoxysilane to deionized water is 1:4-8.
[0049] More preferably, in step S2, the volume ratio of ethyl orthosilicate to 3-aminopropyltriethoxysilane is 1:3-7.
[0050] Preferably, the production of low-loss ultrafine soft magnetic alloy powder is specifically as follows:
[0051] S1. Iron, nickel, manganese, aluminum, silicon and chromium are smelted into alloy at high temperature, and the metal is heated to boiling point by evaporation condensation method, and then steam cooled to obtain ultrafine alloy powder with a D50 particle size of 100-3000nm;
[0052] S2. At 50-60°C, the ultrafine alloy powder prepared in step S1 is added to a medium-temperature zinc-manganese phosphating solution, a phosphating aid is added, the mixture is stirred at a rate of 100-300 r / min for 10-30 min, allowed to stand for 5-15 min, filtered, rinsed with pure water for 2-5 times, anhydrous ethanol is added, stirred at a speed of 400-600 r / min, 3-aminopropyltriethoxysilane and deionized water are added, ethyl orthosilicate is added, the mixture is reacted at 40-60°C for 2-5 h, washed with anhydrous ethanol for 2-5 times, filtered, and dried to obtain a low-loss ultrafine soft magnetic alloy powder.
[0053] More preferably, in step S1, the mass ratio of iron powder to nickel powder is 1:1-2.
[0054] More preferably, in step S1, the mass ratio of iron to manganese is 1:0.001-0.02.
[0055] More preferably, in step S1, the mass ratio of iron to aluminum is 1:0.001-0.02.
[0056] More preferably, in step S1, the mass ratio of iron to silicon is 1:0.001-0.02.
[0057] More preferably, in step S1, the mass ratio of iron to chromium is 0.001-0.02.
[0058] More preferably, in step S2, the mass concentration of the medium-temperature zinc-manganese phosphating solution is 5-10%, and the usage ratio of the ultrafine alloy powder to the medium-temperature zinc-manganese phosphating solution is 1 g: 1-2 mL.
[0059] More preferably, in step S2, the usage ratio of the ultrafine alloy powder to anhydrous ethanol is 1 g: 5-10 mL.
[0060] More preferably, in step S2, the volume ratio of 3-aminopropyltriethoxysilane to anhydrous ethanol is 1:30-40.
[0061] More preferably, in step S2, the volume ratio of 3-aminopropyltriethoxysilane to deionized water is 1:4-8.
[0062] More preferably, in step S2, the volume ratio of ethyl orthosilicate to 3-aminopropyltriethoxysilane is 1:3-7.
[0063] More preferably, in step S2, the phosphating aid comprises a sodium sulfonate derivative, and the mass ratio of the ultrafine alloy powder to the sodium sulfonate derivative is 1:0.01-0.03.
[0064] Preferably, in the manufacture of low-loss ultrafine soft magnetic alloy powder, the phosphating aid includes sodium sulfonate derivatives and acyl phosphite derivatives, the mass ratio of ultrafine alloy powder to sodium sulfonate derivatives is 1:0.01-0.03, and the mass ratio of ultrafine alloy powder to acyl phosphite derivatives is 1:0.005-0.02. Acyl phosphite derivatives improve the stability of the phosphating solution to obtain a phosphating layer with a good coating effect, thereby optimizing the soft magnetic properties of the low-loss ultrafine soft magnetic alloy powder, further improving the resistivity of the low-loss ultrafine soft magnetic alloy powder, and reducing power loss.
[0065] More preferably, the preparation of the acyl phospholipid derivative is specifically,
[0066] Take phosphoethanolamine, add isobutyric anhydride under vacuum and 40-60°C, stir evenly, react at 80-100°C for 2-5h, add diethanolamine, react at 90-100°C for 6-12h to obtain acyl phosphoester derivatives.
[0067] More preferably, the usage ratio of isobutyric anhydride to phosphoethanolamine is 1 mL: 1-5 g.
[0068] More preferably, the mass ratio of diethanolamine to phosphoethanolamine is 1:0.5-1.0.
[0069] The invention also discloses low-loss ultrafine soft magnetic alloy powder prepared by the method.
[0070] The invention also discloses the application of low-loss ultrafine soft magnetic alloy powder in preparing high-performance inductors.
[0071] The invention uses iron, nickel, manganese, aluminum, silicon and chromium to prepare alloy powder, uses sodium sulfonate derivatives and acyl phosphite derivatives as phosphating aids to participate in the phosphating action of medium-temperature zinc-manganese phosphating solution to form a phosphating layer on the surface of the alloy powder; and then uses 3-aminopropyltriethoxysilane and ethyl orthosilicate to wrap a silicon dioxide insulating layer on the surface of the alloy powder to prepare low-loss ultrafine soft magnetic alloy powder, thereby having the following beneficial effects: the low-loss ultrafine soft magnetic alloy powder prepared by the invention has a small D50 particle size of 100-3000nm; a high resistivity of 9.0-18.2Ω·cm; and a low power loss of 282.3-320.3mW / cm 3 Therefore, the present invention discloses a low-loss ultrafine soft magnetic alloy powder with high resistivity and low power loss, and a manufacturing method and application thereof. BRIEF DESCRIPTION OF THE DRAWINGS
[0072] Figure 1 This is the SEM image of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1.
[0073] Figure 2 This is the iron element distribution of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1.
[0074] Figure 3 This is the nickel element distribution of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1.
[0075] Figure 4 This is the manganese element distribution of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1.
[0076] Figure 5 The silicon element distribution of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1.
[0077] Figure 6 This is the oxygen element distribution of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1. DETAILED DESCRIPTION
[0078] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0079] The experimental methods in the following examples are conventional methods unless otherwise specified. The materials, reagents, etc. used in the following examples are commercially available unless otherwise specified.
[0080] Embodiment 1:
[0081] Manufacturing of low-loss ultrafine soft magnetic alloy powders, including,
[0082] S1. Iron, nickel, manganese, aluminum, silicon and chromium are smelted into alloy at high temperature, and the metal is heated to boiling point by evaporation condensation method, and then steam cooled to obtain ultrafine alloy powder with a D50 particle size of 750nm. The mass ratio of iron to nickel is 1:1; the mass ratio of iron to manganese is 1:0.01, the mass ratio of iron to aluminum is 1:0.01, the mass ratio of iron to silicon is 1:0.01, and the mass ratio of iron to chromium is 0.01;
[0083] S2. At 55°C, add anhydrous ethanol to the ultrafine alloy powder prepared in step S1, stir at a speed of 500 r / min, add 3-aminopropyltriethoxysilane and deionized water, add ethyl orthosilicate, react at 50°C for 3 hours, wash with anhydrous ethanol 3 times, filter and dry to obtain low-loss ultrafine soft magnetic alloy powder. The dosage ratio of ultrafine alloy powder and anhydrous ethanol is 1g:8.5mL; the volume ratio of 3-aminopropyltriethoxysilane and anhydrous ethanol is 1:34; the volume ratio of 3-aminopropyltriethoxysilane and deionized water is 1:6; the volume ratio of ethyl orthosilicate and 3-aminopropyltriethoxysilane is 1:5.
[0084] Embodiment 2:
[0085] Manufacturing of low-loss ultrafine soft magnetic alloy powders, including,
[0086] S1. Iron, nickel, manganese, aluminum, silicon and chromium are smelted into alloy at high temperature, and the metal is heated to boiling point by evaporation condensation method, and then steam cooled to obtain ultrafine alloy powder with a D50 particle size of 750nm. The mass ratio of iron to nickel is 1:1; the mass ratio of iron to manganese is 1:0.01, the mass ratio of iron to aluminum is 1:0.01, the mass ratio of iron to silicon is 1:0.01, and the mass ratio of iron to chromium is 0.01;
[0087] S2. At 55°C, add the ultrafine alloy powder prepared in step S1 to a medium-temperature zinc-manganese phosphating solution, stir at a rate of 200 r / min for 20 min, let stand for 5 min, filter, rinse with pure water 3 times, add anhydrous ethanol, stir at a speed of 500 r / min, add 3-aminopropyltriethoxysilane and deionized water, add ethyl orthosilicate, react at 50°C for 3 h, wash with anhydrous ethanol 3 times, filter, and dry to obtain low-loss ultrafine soft magnetic alloy powder. Medium-temperature zinc-manganese phosphating solution was purchased from Beijing Ailsme Technology Co., Ltd. The mass concentration of the medium-temperature zinc-manganese phosphating solution was 10%, the dosage ratio of ultrafine alloy powder to medium-temperature zinc-manganese phosphating solution was 1 g:1 mL; the dosage ratio of ultrafine alloy powder to anhydrous ethanol was 1 g:8.5 mL; the volume ratio of 3-aminopropyltriethoxysilane to anhydrous ethanol was 1:34; the volume ratio of 3-aminopropyltriethoxysilane to deionized water was 1:6; the volume ratio of ethyl orthosilicate to 3-aminopropyltriethoxysilane was 1:5.
[0088] Embodiment 3:
[0089] Preparation of sodium sulfonate derivatives, comprising:
[0090] Weigh azelayl chloride, add dichloromethane and stir to dissolve, add 1-octen-3-ol and triethylamine, stir to react for 8 hours, add sodium carbonate solution to adjust the pH to neutral, add sodium bisulfite and deionized water, react at 140°C for 3 hours, add methanol, filter, rotary evaporate, and dry to obtain the sodium sulfonate derivative. The molar ratio of azelayl chloride to dichloromethane is 1 mol: 350 mL; the molar ratio of 1-octen-3-ol to azelayl chloride is 1: 1.5; the molar ratio of triethylamine to azelayl chloride is 1: 1.5; the molar ratio of azelayl chloride to sodium bisulfite is 1: 1; the molar ratio of azelayl chloride to deionized water is 1 mol: 180 mL; the volume ratio of deionized water to methanol is 1: 1.
[0091] Manufacturing of low-loss ultrafine soft magnetic alloy powders, including,
[0092] S1. Iron, nickel, manganese, aluminum, silicon and chromium are smelted into alloy at high temperature, and the metal is heated to boiling point by evaporation condensation method, and then steam cooled to obtain ultrafine alloy powder with a D50 particle size of 750nm. The mass ratio of iron to nickel is 1:1; the mass ratio of iron to manganese is 1:0.01, the mass ratio of iron to aluminum is 1:0.01, the mass ratio of iron to silicon is 1:0.01, and the mass ratio of iron to chromium is 0.01;
[0093] S2. At 55°C, add the ultrafine alloy powder prepared in step S1 to a medium-temperature zinc-manganese phosphating solution, add a sodium sulfonate derivative, stir at a rate of 200 r / min for 20 min, let stand for 5 min, filter, rinse with pure water 3 times, add anhydrous ethanol, stir at a speed of 500 r / min, add 3-aminopropyltriethoxysilane and deionized water, add ethyl orthosilicate, react at 50°C for 3 h, wash with anhydrous ethanol 3 times, filter, and dry to obtain a low-loss ultrafine soft magnetic alloy powder. Medium-temperature zinc-manganese phosphating solution was purchased from Beijing Ailsmu Technology Co., Ltd. The mass concentration of the medium-temperature zinc-manganese phosphating solution was 10%, the dosage ratio of ultrafine alloy powder to medium-temperature zinc-manganese phosphating solution was 1 g:1 mL; the mass ratio of ultrafine alloy powder to sodium sulfonate derivative was 1:0.03; the dosage ratio of ultrafine alloy powder to anhydrous ethanol was 1 g:8.5 mL; the volume ratio of 3-aminopropyltriethoxysilane to anhydrous ethanol was 1:34; the volume ratio of 3-aminopropyltriethoxysilane to deionized water was 1:6; the volume ratio of ethyl orthosilicate to 3-aminopropyltriethoxysilane was 1:5.
[0094] Embodiment 4:
[0095] The difference between this embodiment and embodiment 3 is only the production of low-loss ultrafine soft magnetic alloy powder.
[0096] In this embodiment, except that the mass ratio of the ultrafine alloy powder to the sodium sulfonate derivative is changed to 1:0.01 in the manufacture of the low-loss ultrafine soft magnetic alloy powder, other conditions are the same as those in Embodiment 3.
[0097] Embodiment 5:
[0098] Preparation of acylphospholipid derivatives, comprising:
[0099] Take ethanolamine phosphate, add isobutyric anhydride under vacuum and 50°C, stir evenly, react at 90°C for 3h, add diethanolamine, react at 95°C for 8h, and obtain acyl phosphoester derivatives. The dosage ratio of isobutyric anhydride to ethanolamine phosphate is 1mL:2g; the mass ratio of diethanolamine to ethanolamine phosphate is 1:0.65.
[0100] Preparation of sodium sulfonate derivatives, comprising:
[0101] Weigh azelayl chloride, add dichloromethane and stir to dissolve, add 1-octen-3-ol and triethylamine, stir to react for 8 hours, add sodium carbonate solution to adjust the pH to neutral, add sodium bisulfite and deionized water, react at 140°C for 3 hours, add methanol, filter, rotary evaporate, and dry to obtain the sodium sulfonate derivative. The molar ratio of azelayl chloride to dichloromethane is 1 mol: 350 mL; the molar ratio of 1-octen-3-ol to azelayl chloride is 1: 1.5; the molar ratio of triethylamine to azelayl chloride is 1: 1.5; the molar ratio of azelayl chloride to sodium bisulfite is 1: 1; the molar ratio of azelayl chloride to deionized water is 1 mol: 180 mL; the volume ratio of deionized water to methanol is 1: 1.
[0102] Manufacturing of low-loss ultrafine soft magnetic alloy powders, including,
[0103] S1. Iron, nickel, manganese, aluminum, silicon and chromium are smelted into alloy at high temperature, and the metal is heated to boiling point by evaporation condensation method, and then steam cooled to obtain ultrafine alloy powder with a D50 particle size of 750nm. The mass ratio of iron to nickel is 1:1; the mass ratio of iron to manganese is 1:0.01, the mass ratio of iron to aluminum is 1:0.01, the mass ratio of iron to silicon is 1:0.01, and the mass ratio of iron to chromium is 0.01;
[0104] S2. At 55°C, add the ultrafine alloy powder prepared in step S1 to a medium-temperature zinc-manganese phosphating solution, add acyl phosphide derivatives and sodium sulfonate derivatives, stir at a rate of 200 r / min for 20 min, let stand for 5 min, filter, rinse with pure water 3 times, add anhydrous ethanol, stir at a speed of 500 r / min, add 3-aminopropyltriethoxysilane and deionized water, add ethyl orthosilicate, react at 50°C for 3 h, wash with anhydrous ethanol 3 times, filter, and dry to obtain low-loss ultrafine soft magnetic alloy powder. Medium-temperature zinc-manganese phosphating solution was purchased from Beijing Ailsmu Technology Co., Ltd. The mass concentration of the medium-temperature zinc-manganese phosphating solution was 10%, the amount ratio of ultrafine alloy powder to medium-temperature zinc-manganese phosphating solution was 1 g:1 mL; the mass ratio of ultrafine alloy powder to sodium sulfonate derivative was 1:0.03; the mass ratio of ultrafine alloy powder to acyl phosphite derivative was 1:0.02; the amount ratio of ultrafine alloy powder to anhydrous ethanol was 1 g:8.5 mL; the volume ratio of 3-aminopropyltriethoxysilane to anhydrous ethanol was 1:34; the volume ratio of 3-aminopropyltriethoxysilane to deionized water was 1:6; the volume ratio of ethyl orthosilicate to 3-aminopropyltriethoxysilane was 1:5.
[0105] Embodiment 6:
[0106] The difference between this embodiment and embodiment 5 is only the production of low-loss ultrafine soft magnetic alloy powder.
[0107] In this embodiment, except that the mass ratio of the ultrafine alloy powder to the acyl phosphite derivative is changed to 1:0.005 in the manufacture of the low-loss ultrafine soft magnetic alloy powder, other conditions are the same as those of Embodiment 5.
[0108] Comparative Example 1:
[0109] The difference between this comparative example and Example 4 is only the production of low-loss ultrafine soft magnetic alloy powder.
[0110] In this embodiment, except that no sodium sulfonate derivative is added in the manufacture of the low-loss ultrafine soft magnetic alloy powder, other conditions are the same as those of Example 4.
[0111] Experimental example:
[0112] 1. Material Characterization
[0113] The surface morphology of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1 was observed using a scanning electron microscope, and the element distribution analysis was performed using an electron probe provided in the electron microscope.
[0114] Figure 1 This is a SEM image of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1, with a scale of 100 nm. The low-loss ultrafine soft magnetic alloy powder prepared in Example 1 is in the form of round particles with a smooth surface and a protective layer. Figure 2 The iron element distribution of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1, the scale is 100nm; Figure 3 The nickel element distribution of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1, the scale is 100nm; Figure 4 The manganese element distribution of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1, the scale is 100nm; Figure 5 The silicon element distribution of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1, the scale is 100nm; Figure 6 This is the oxygen element distribution of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1, with a scale of 100 nm; iron, nickel, manganese, silicon and oxygen elements are evenly distributed on the surface of the low-loss ultrafine soft magnetic alloy powder prepared in Example 1, which indicates that the low-loss ultrafine soft magnetic alloy powder prepared in Example 1 of the present invention is effectively coated with a silicon dioxide protective layer.
[0115] 2. Resistivity
[0116] The resistivity (Ω·cm) of the low-loss ultrafine soft magnetic alloy powders prepared in Examples 1-6 and Comparative Example 1 was measured using the four-probe method. Resistivity (Ω·cm) = (cross-sectional area × voltage across a standard resistor × resistance of a standard resistor) / (voltage across low-loss ultrafine soft magnetic alloy powder × distance). The resistivity measurement results are shown in Table 1.
[0117] Table 1 Resistivity (Ω·cm)
[0118]
[0119] As can be seen from Table 1, the resistivity of Example 2 of the present invention is higher than that of Example 1, because in the manufacture of low-loss ultrafine soft magnetic alloy powder, Example 2 first uses a medium-temperature zinc-manganese phosphating solution for phosphating treatment, and then coats the silicon dioxide layer, while Example 1 does not use a medium-temperature zinc-manganese phosphating solution for phosphating treatment; the resistivity of Examples 3-4 is higher than that of Example 2, because in the manufacture of low-loss ultrafine soft magnetic alloy powder, Examples 3-4 use sodium sulfonate derivatives, while Example 2 does not use sodium sulfonate derivatives; the resistivity of Example 3 is higher than that of Example 4, because in the manufacture of low-loss ultrafine soft magnetic alloy powder, the amount of sodium sulfonate derivatives used is different. This shows that in the manufacture of low-loss ultrafine soft magnetic alloy powder, the use of an appropriate amount of sodium sulfonate derivatives to assist the phosphating effect of the medium-temperature zinc-manganese phosphating solution can improve the resistivity of the low-loss ultrafine soft magnetic alloy powder.
[0120] The resistivity of Examples 5-6 of the present invention is higher than that of Examples 3 and Comparative Example 1 because, in the manufacture of low-loss ultrafine soft magnetic alloy powder, Examples 5-6 use acyl phosphide derivatives and sodium sulfonate derivatives in synergy, while Example 3 only uses sodium sulfonate derivatives, and Comparative Example 1 only uses acyl phosphide derivatives; the resistivity of Example 5 is higher than that of Example 6 because the amount of acyl phosphide derivatives used in the manufacture of low-loss ultrafine soft magnetic alloy powder is different. This shows that in the manufacture of low-loss ultrafine soft magnetic alloy powder, the synergistic use of acyl phosphide derivatives and sodium sulfonate derivatives to assist the phosphating effect of the medium-temperature zinc-manganese phosphating solution can further improve the resistivity of the low-loss ultrafine soft magnetic alloy powder.
[0121] 3. Power loss
[0122] The power loss of the low-loss ultrafine soft magnetic alloy powders prepared in Examples 1-6 and Comparative Example 1 was measured at 50 kHz / 50 mT using a SY-8232B-H analyzer. The measurement results are shown in Table 2.
[0123] Table 2 Power loss (mW / cm 3 )
[0124]
[0125] As can be seen from Table 2, the power loss of Example 2 of the present invention is lower than that of Example 1, because in the manufacture of low-loss ultrafine soft magnetic alloy powder, Example 2 first uses a medium-temperature zinc-manganese phosphating solution for phosphating treatment, and then coats the silicon dioxide layer, while Example 1 does not use a medium-temperature zinc-manganese phosphating solution for phosphating treatment; the power loss of Examples 3-4 is lower than that of Example 2, because in the manufacture of low-loss ultrafine soft magnetic alloy powder, Examples 3-4 use sodium sulfonate derivatives, while Example 2 does not use sodium sulfonate derivatives; the power loss of Example 3 is lower than that of Example 4, because in the manufacture of low-loss ultrafine soft magnetic alloy powder, the amount of sodium sulfonate derivatives used is different. This shows that in the manufacture of low-loss ultrafine soft magnetic alloy powder, the use of an appropriate amount of acyl phosphite derivatives to assist the phosphating effect of the medium-temperature zinc-manganese phosphating solution can reduce the power loss of the low-loss ultrafine soft magnetic alloy powder.
[0126] The power loss of Examples 5-6 of the present invention is lower than that of Examples 3 and Comparative Example 1 because, in the manufacture of low-loss ultrafine soft magnetic alloy powder, Examples 5-6 use acyl phosphide derivatives and sodium sulfonate derivatives in coordination, while Example 3 only uses sodium sulfonate derivatives, and Comparative Example 1 only uses acyl phosphide derivatives; the power loss of Example 5 is lower than that of Example 6 because the amount of acyl phosphide derivatives used in the manufacture of low-loss ultrafine soft magnetic alloy powder is different. This shows that in the manufacture of low-loss ultrafine soft magnetic alloy powder, the coordinated use of acyl phosphide derivatives and sodium sulfonate derivatives to assist the phosphating effect of the medium-temperature zinc-manganese phosphating solution can further reduce the power loss of the low-loss ultrafine soft magnetic alloy powder.
[0127] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here.
[0128] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for producing low-loss ultrafine soft magnetic alloy powder, comprising: S1. Iron, nickel, manganese, aluminum, silicon and chromium are smelted into an alloy at high temperature, and the alloy is heated to boiling point by evaporation condensation method, and then steam cooled to obtain ultrafine alloy powder with a D50 particle size of 100-3000nm; S2, reacting the ultrafine alloy powder with a medium-temperature zinc-manganese phosphating solution and a phosphating aid, and then reacting with 3-aminopropyltriethoxysilane and ethyl orthosilicate to obtain a low-loss ultrafine soft magnetic alloy powder; The phosphating auxiliary agent includes a sodium sulfonate derivative and an acyl phosphite derivative, wherein the sodium sulfonate derivative has a sulfonic acid group, a benzene ring and a vinyl group; in the preparation of the sodium sulfonate derivative, azelaic acid chloride is weighed, dichloromethane is added and stirred to dissolve, 1-octen-3-ol and triethylamine are added, stirred to react for 6-12 hours, sodium carbonate solution is added to adjust the pH to neutral, sodium bisulfite and deionized water are added, reacted at 120-160° C. for 2-5 hours, methanol is added, filtered, rotary evaporated, and dried to obtain the sodium sulfonate derivative; in the preparation of the acyl phosphite derivative, ethanolamine is taken, isobutyric anhydride is added under vacuum and 40-60° C., stirred evenly, reacted at 80-100° C. for 2-5 hours, diethanolamine is added, reacted at 90-100° C. for 6-12 hours, and the acyl phosphite derivative is obtained.
2. The method for producing low-loss ultrafine soft magnetic alloy powder according to claim 1, characterized in that: The mass ratio of iron to nickel is 1:1-2, the mass ratio of iron to manganese is 1:0.001-0.02, the mass ratio of iron to aluminum is 1:0.001-0.02, the mass ratio of iron to silicon is 1:0.001-0.02, and the mass ratio of iron to chromium is 0.001-0.
02.
3. The method for producing low-loss ultrafine soft magnetic alloy powder according to claim 1, characterized in that: The mass concentration of the medium-temperature zinc-manganese phosphating solution is 5-10%, and the dosage ratio of the ultrafine alloy powder to the medium-temperature zinc-manganese phosphating solution is 1g:1-2mL.
4. The method for producing low-loss ultrafine soft magnetic alloy powder according to claim 1, characterized in that: The usage ratio of the ultrafine alloy powder to 3-aminopropyltriethoxysilane is 1g:0.1-0.5mL.
5. The method for producing low-loss ultrafine soft magnetic alloy powder according to claim 1, characterized in that: The volume ratio of the ethyl orthosilicate to 3-aminopropyltriethoxysilane is 1:2-10.
6. The method for producing low-loss ultrafine soft magnetic alloy powder according to claim 1, characterized in that: The molar ratio of azelaic acid chloride to 1-octen-3-ol is 1:1-2.
7. The method for producing low-loss ultrafine soft magnetic alloy powder according to claim 1, characterized in that: The molar ratio of azelayl chloride to sodium bisulfite is 1:1-2.
8. Low-loss ultrafine soft magnetic alloy powder produced by the production method described in any one of claims 1 to 7.
9. Use of the low-loss ultrafine soft magnetic alloy powder described in claim 8 in the preparation of high-performance inductors.
Citation Information
Patent Citations
Cadmium-free lead-free super-fine zinc alloy powder and preparation method thereof
CN104988353A
Environmentally friendly anti-corrosion phosphatizing liquid and preparation method thereof
CN105908165A
Low-loss iron-nickel soft magnetic powder and preparation method thereof
CN115985614A